Development of the Use of Artificial Intelligence (AI) Technology and Jakarta Smart City (JSC) - Taufiqurokhman; Murod, Ma’mun; Wibisono, Dany Kunto; Sasanti, Dyah Nur; Chandranegara, Ibnu Sina; Akram, Muhammad (Yayasan Ilomata, 2024)
The research aims to explain the use of Artificial Intelligence (AI) and Jakarta Smart City (JSC) technology, which was first implemented in Indonesia in 2014, starting in the Jakarta City Region (DKJ), followed by 100 cities, carried out to overcome the technology gap between regions. Use of AI and JSC by the government for public services, such as smart environment; people's economy; government; population mobility, and branding. Research methodology uses qualitative with a descriptive approach using observation instruments and direct interviews. The research period is three months (March to April 2024). Locations in seven JSC management units. The research population was in five JSC divisions, using a snowball pattern sample. The research results show that there has been an increase in the efficiency of public services using AI and JSC technology in transportation management; rubbish; city ​​security defense; and improving the quality of resources. Traffic congestion research recommendations, DKJ must develop innovations for all integrated public transportation facilities, by expanding the Integrated Highway (MRT) and Light Rail Transit (LRT) networks. For flooding problems, DKJ must use early digital detection technology for flood monitoring. In the future, DKJ hopes to implement an integrated digital payment system between the Resident Card and: Taxpayer Identification Number (NPWP), digital lifetime extension of the Driving License (SIM), processing of annual Vehicle Registration Certificates (STNK), and Vehicle Tax Proof Bermptor (BPKB) five-yearly all two-wheeled vehicles online (digitally) without queuing at the location.